DETERMINAN NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - May, Florencia; Susanto, Liana (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study is to obtain empirical evidence about factors affecting firm value in manufacturing companies listed on Indonesia Stock Exchange for the years 2017-2019. Sample selection technique that used is purposive sampling method and acquired 78 companies. Data processing technique using multiple linear regression analysis with the Eviews 12 software. The results showed that profitability has positive significant effect on firm value, liquidity has negative significant effect on firm value, while leverage, firm size, and CSR do not have significant effect on firm value. The implication of this research is to provide information for investors that should study the company's financial statements carefully before decided to invest in a company.